Tribological mechanism of diamond-like carbon films induced by Ti/Al co-doping - Kong, Cuicui; Guo, Peng; Sun, Lili; Zhou, Yong; Liang, Yunxiao; Li, Xiaowei; Ke, Peiling; Lee, Kwang-Ryeol; Wang, Aiying (ELSEVIER SCIENCE SA, 2018)
Co-doping two metals into diamond-like carbon (DLC) films exhibits a desirable combination of low residual stress and hard hardness for further application, but the insight into tribological mechanism induced by the co-doped metals is still not fully clarified yet. In this work, we fabricated the Ti/Al co-doped DLC films (Ti/Al-DLC) with various metal concentrations using the hybrid ion beam system, and the tribological properties of films were systematically investigated. Results revealed that the co-doped Ti/Al metals played an important role in the tribological behaviors of DLC films; the film deposited at 2.5 A (Ti10.06at.%Al4.78at.%) exhibited the lowest friction coefficient of about 0.05 and wear rate of 1.56 x 10(-16) m(3) N-1 m(-1). This attributed to the formation of thick transfer layer in the friction interface, which could be described as a dual or hierarchy nanostructure constructed of cross-linking amorphous carbon networks and hard phase (mainly TiC and Al2O3) structures.
Keywords: NANOCOMPOSITE TIALC COATINGS; AMORPHOUS-CARBON; DLC COATINGS; ION-BEAM; TRIBOFILM FORMATION; BIAS VOLTAGE; THIN-FILMS; AB-INITIO; MICROSTRUCTURE; DEPOSITION